Studi Komparasi Antara Model Pembelajaran Matematika Realistik dengan Model Pembelajaran Konvensional Terhadap Prestasi Belajar Siswa MI Walisongo Kebonrowopucang Pekalongan - Ismiati, Nur; Mustakim, Zaenal (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
Mathematics is still considered a difficult subject. For this reason, in learning mathematics, it is necessary to apply a learning model that connects learning concepts so that students' lives are closer. The purpose of this study was to determine the difference in learning achievement between classes using conventional learning models and classes using PMR (Realistic Mathematics Learning) models in the mathematics learning process at MI Kebonrowopucang Pekalongan. This research is a quasi-experimental research type with a quantitative approach. Data collection techniques were carried out by test and documentation methods. The data obtained were then analyzed using the independent sample t-test analysis technique. The sampleof this research is all students of class IV A and IV B at MI Walisongo Kebonrowopucang Karangdadap. The results of this study indicate that tcount > ttable (tcount = 5,777, ttable = 2,000), then H0 is rejected and Ha is accepted. Thus, it can be concluded that there is a significant difference in students' mathematics learning achievement between those using realistic mathematics learning models and those using conventional learning models and the PMR (Realistic Mathematics Learning) learning model is better than conventional learning models.